Does Quality of Audit to Become Roles at Accountant Professional Indonesia - Yartono, Nungki; Asyari; Ramli, Muhammad; Pallawagau, Andi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The research examines the influence of professional ethics, independence, and accountability variables on audit quality. The sample and research population are analyzed using statistical techniques and then interpreted using the quantitative descriptive research method. Quantitative research is used for variables that are the object of research. Data as a research instrument was analyzed according to the hypothesis and processed using the SPSS 25 application. The data used in this research was primary, and questionnaires were used for the data collection method. Data was collected using a questionnaire distributed using Google Forms to auditors who work at KAP in Jakarta. The number of samples processed was 82 respondents. The hypothesis analysis test was processed using a linear regression model partial t-test and simultaneous F-test. The research results, according to the t-test, illustrate that professional ethics has a significant effect on audit quality, independent auditors have a significant impact on audit quality, and accountability has a significant effect on audit quality.